The use of tobit model in evaluating prospective participatory financing of rehabilitation of Ibadan urban forest reserves (2003)
This study evaluated the factors that affect public willingness to participate financially in the rehabilitation of Ibadan urban forest reserves. A one limit Tobit model was used to analyse data obtained from a multi-stage randomly sampled 397 residents of Ibadan metropolis. The results show that 90% of the respondents were willing to contribute funds to the project. Furthermore, the model reveals that a change in the independent variables would lead to a greater change (77%) in the probability of contributing money, relative to change (23%) in the amount of money to be contributed. Willingness to participate financially in rehabilitation of Ibadan urban forest reserves was found to be positively influenced by the variables: being employed,(p < 0.01). having trees in the residence (p < 0.01), and being a past beneficiary of the forests (p<0.05). 'S he results confirm the need to make the urban forest more directly beneficial to the public in order to harness the funds which the public is willing to contribute to its rehabilitation.